Will and Choice in Aristotle - Vélez, Ysis (Disertaciones, 2017)
The subject of responsibility is undertaken by Aristotle from the perspective of the evaluation of the voluntary and involuntary actions in morals as well as in civil and penal spheres. My purpose is to carry out an investigation of the concepts of bou9lhsij and proai9resij, by showing the doctrinal divergences between N.E and E.E. If we consider that the Stagirite attempts a new approach that objects to Socrates and Euripides’ traditions whom accentuate the determinism and fatality of our actions; Aristotle destroys the excuses of involuntariness as an initial condition of the responsibility and assigns a predominant role to the proai9resij as a necessary and sufficient condition to make a man the master of his actions and so, competent to take responsibility before himself and his fellow citizens. These concepts are tackled form the context of the moral investigation or a9reth9, since although the disciple of Plato will assign a preeminent place to the political and civic life, he considers as a presupposition of such hierarchy the comings and goings of the goodness of character whose practice concerns the most to the good man than to the polith9j.
Keywords: Will; Choice; Wish; Reason; Desire; Anger